Fostering Students' Physical Literacy through Academic Conversations: Using Think-Pair-Share as a Teaching Strategy in Physical Education. (4th May 2022) - Lynott, Francis J.; Nelson, Tracy; Oh, Hyun-Ju
Abstract: According to SHAPE America, the goal of physical education "is to develop physically literate individuals." Whitehead suggests that physically literate is a process that can be enriched with the development of the cognitive and affective learning domains through academic conversations. Although common to other content areas, the Think-Pair-Share teaching strategy in physical education is unique and can be utilized to develop Physical Literacy. Think-Pair-Share can be an effective way to engage students in academic conversations to achieve physical literacy and enrich a quality physical education with a little planning. This article introduces the Think-Pair-Share to foster students' physical literacy using a three-phase strategy.